Tek doz sertralin kullanımıyla ortaya çıkan bir panik atak olgusu - Korkmaz, Sevda; Kuloğlu, Murat; Işık, Umuıt; Namlı, Mustafa Nuray; Korkmaz, Hasan; Atmaca, Murad (My University, 2010)
-
Keywords: Psikiyatri